Pendidikan Sains dalam Al-Quran (Studi Penafsiran Quraish Shihab terhadap Q.S. Al-Baqarah: 26) - - Derhana Bulan Dalimunthe; - H. Rusli (Akademika: Jurnal Keagamaan dan Pendidikan, 2019)
Al-Qur‟an is a promoter to muslim community, finding and developing of knowledge. Al-Qur‟an is believed embrace all knowledge include science. This paper is contain tafsir of quraish shihab about surah al-Baqarah: 26 and relation of science. As one of the evidence the interpretation that manage to correlate two scientific knowledge. The interpretation of this ayat he had differ with others mufassir. Begin from the mention about how hazardous an mosquito, as long as the time is considered small and unimportant by all many people, particularly in this ayat is intended to hypocrite people (munafik). This interpretation afterwards corelated with scientists perspective.